2009
DOI: 10.1002/chem.200801704
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Copper Oxide on Silica–Zirconia Mixed Oxides by Chemical Implantation

Abstract: cis‐2,5‐Disubstituierte Pyrrolidin‐Grundgerüste sind durch eine Pd0‐katalysierte Drei‐Komponenten‐Tandem‐Doppelcyclisierung aus 2‐(2,3‐Butadienyl)malonaten, Organohalogeniden und Iminen zugänglich (siehe Schema; Ausbeuten: 81–100 %, cis/trans >95:5).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…Recently, the study of the reactivity of homoleptic N,N-dialkylcarbamates with silica has been extended to Cu(II), Nb(III), Nb(V), Ta(V), Tb(III) and Eu(III) derivatives [131,153,362,363]. Silica grafting has been also realized with non-homoleptic complexes of group 4 and 5 metals, wherein the carbamato ligands are the most reactive ones [166,234,290].…”
Section: Other Applicationsmentioning
confidence: 99%
“…Recently, the study of the reactivity of homoleptic N,N-dialkylcarbamates with silica has been extended to Cu(II), Nb(III), Nb(V), Ta(V), Tb(III) and Eu(III) derivatives [131,153,362,363]. Silica grafting has been also realized with non-homoleptic complexes of group 4 and 5 metals, wherein the carbamato ligands are the most reactive ones [166,234,290].…”
Section: Other Applicationsmentioning
confidence: 99%
“…It has been shown that cationic implantation onto silica can be effectively carried out with group‐four metals, niobium and tantalum, tin(IV), palladium(II), platinum(II), gold(I), copper(II) and lanthanides, by using N , N ‐dialkylcarbamato complexes of the general formula M(O 2 CNR 2 ) n as precursors.…”
Section: Resultsmentioning
confidence: 99%
“…Metal carbamates are an intriguing class of compounds that have been found to be suitable precursors to homogeneous catalysts, chemical vapour deposition and materials chemistry . There is currently interest in expanding the family of metal–carbamato complexes to mixed halido‐carbamates.…”
Section: Resultsmentioning
confidence: 99%